Elevated levels of serum transforming growth factor-β 1 in oesophageal squamous cell carcinoma patients - Diakowska, Dorota; Lewandowski, Andrzej; Markocka-Mączka, Krystyna; Grabowski, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2011)
Background : Transforming growth factor- β 1 (TGF- β 1) is a multifunctional cytokine involved in cancer development. The diagnostic significance of serum levels of transforming growth factor- β 1 (sTGF- β 1) in the oesophageal squamous cell carcinoma (ESCC) remains unclear. The aim of the study was to analyze sTGF- β 1 concentrations in ESCC patients. The sTGF- β 1 levels were assessed according to the clinical parameters in cancer patients. We determined sTGF- β 1 concentrations in ESCC patients before and after oesophagectomy. The correlation between sTGF- β 1 and serum levels of vascular endothelial growth factor (sVEGF-A) was examined as well. Material and methods: The study included 115 patients with ESCC and 57 healthy controls. Concentrations of sTGF- β 1 were measured by ELISA tests and were compared with clinical parameters of cancer patients. Serum samples for sTGF- β 1 evaluation 3 months after surgical resection were available in 41 cases. Results : Serum TGF- β 1 level was significantly higher in ESCC compared to the control group (p < 0.001). Serum levels of TGF- β 1 positively correlated with the depth of tumour invasion (p = 0.042). There were no differences in sTGF- β 1 levels in patients stratified by the presence of regional and distant metastases and stage of cancer progression. The level of sTGF- β 1 was significantly lower in ESCC patients after oesophagectomy than before surgical treatment (p = 0.002). A positive correlation between sTGF- β 1 and sVEGF-A (p = 0.017) was observed.